Global imbalances and the intertemporal external budget constraint: A multicointegration approach - Camarero, Mariam; Carrion-i-Silvestre, Josep Lluís; Tamarit, Cecilio (Journal of Banking & Finance, 2013)
This paper analyzes the external solvency of a group of 23 OECD countries for the period 1970–2012. The empirical strategy adopted underlines the increasing importance of the financial channel for the external adjustment as proposed in Gourinchas and Rey (2007). We unify the traditional approaches to testing for external sustainability considering the stock-flow system created by the variables representing the external relationships of an open economy. External sustainability is tested using several types of cointegration and multicointegration tests. The results obtained point to weak sustainability in the flows analysis, whereas some degree of strong sustainability is found for up to six countries in the stock-flow approach. Among these countries we find both non-European economies, such as Japan and New Zealand, and Euro-area members, especially those with more restricted access to financing in the international markets.